WORLD TREND ANALYSIS AS A TOOL FOR DEVELOPMENT OF ORGANIC FOOD MARKET IN SERBIA - Zubović, Jovan; Domazet, Ivana (Economics of Agriculture, 2007)
Serbia has in 2006 adopted a Law on "Organic production and organic products". This was a first step towards improvement of this, very prosperous field of agriculture. Unfortunately, in the same year, the state has invested only 50 million diners (600.000 €) for subvention of this production. This was mostly related to licensing of fields for organic production. Unlike that, in neighboring Croatia, which is trailing in organic production to Serbia government has adopted a regulation by which all organic manufacturers are subsidized by 400€ per hectare. This paper analyses trends in the world developed countries in which organic industry is present or over than 15 years and gives directions on how to develop organic industry in Serbia.